A Patternable and In Situ Formed Polymeric Zinc Blanket for a Reversible Zinc Anode in a Skin‐Mountable Microbattery. Issue 8 (14th January 2021) - Zhu, Minshen; Hu, Junping; Lu, Qiongqiong; Dong, Haiyun; Karnaushenko, Dmitriy D.; Becker, Christian; Karnaushenko, Daniil; Li, Yang; Tang, Hongmei; Qu, Zhe; Ge, Jin; Schmidt, Oliver G.
Abstract: Owing to their high safety and reversibility, aqueous microbatteries using zinc anodes and an acid electrolyte have emerged as promising candidates for wearable electronics. However, a critical limitation that prevents implementing zinc chemistry at the microscale lies in its spontaneous corrosion in an acidic electrolyte that causes a capacity loss of 40% after a ten‐hour rest. Widespread anti‐corrosion techniques, such as polymer coating, often retard the kinetics of zinc plating/stripping and lack spatial control at the microscale. Here, a polyimide coating that resolves this dilemma is reported. The coating prevents corrosion and hence reduces the capacity loss of a standby microbattery to 10%. The coordination of carbonyl oxygen in the polyimide with zinc ions builds up over cycling, creating a zinc blanket that minimizes the concentration gradient through the electrode/electrolyte interface and thus allows for fast kinetics and low plating/stripping overpotential. The polyimide's patternable feature energizes microbatteries in both aqueous and hydrogel electrolytes, delivering a supercapacitor‐level rate performance and 400 stable cycles in the hydrogel electrolyte. Moreover, the microbattery is able to be attached to human skin and offers strong resistance to deformations, splashing, and external shock. The skin‐mountable microbattery demonstrates an excellent combination of anti‐corrosion, reversibility, and durability in wearables. Abstract : A zinc blanket created by the coordination between carbonyl oxygen atoms in a polyimide coating and zinc ions overcomes the thermodynamic instability and facilitates plating/stripping kinetics. Patterning this zinc blanket for a Zn microanode allows for the development of a skin‐mountable microbattery with an outstanding rate capability and stable cycling performance, providing promise for microbatteries integrable for electronic skin.